DEVELOPMENT OF AN OPTIMAL METHOD FOR IRON EXTRACTION FROM METALLURGICAL SLAGS (European Journal of Interdisciplinary Research and Development, 2025)
Metallurgical slags generated during steelmaking contain a significant amount of iron in the form of oxides and complex compounds, which represents both a valuable secondary resource and an environmental challenge. This study focuses on the development of an optimal method for the extraction of iron from metallurgical slags through a comprehensive analysis of reduction processes and material interactions. The research investigates the physicochemical properties of steelmaking slags, including phase composition, iron distribution, and granulometric characteristics, to determine favorable conditions for iron recovery. Thermodynamic modeling and experimental reduction studies were carried out using carbon-based and alternative local reducing agents to evaluate their effectiveness in converting iron oxides into metallic iron. The influence of temperature, reduction time, and slag composition on the degree of metallization was systematically analyzed. Microstructural, diffractive, and spectroscopic analyses were employed to characterize phase transformations and the efficiency of iron liberation from the slag matrix. The results demonstrate that optimized reduction parameters significantly enhance iron recovery while minimizing energy consumption and secondary waste formation. The proposed method contributes to improving the resource efficiency of metallurgical processes and promotes the sustainable utilization of secondary technogenic raw materials. The developed approach can be effectively integrated into existing steel production routes, providing both economic and environmental benefits.